HSP70 AND INOS BIOMARKERS IN EVALUATING THE HEALING PROPERTIES OF RUBIA TINCTORUM - Alsarhan, Ali; Mansi, Kamal; Aburjai, Talal; Al-Khatib, Ahed; Alzweiri, Muhammed; Sultana, Naznin (European Scientific Journal, ESJ, 2013)
Introduction: Rubia tinctorum L. (F. Rubiaceae) has historical role in promotion of healing process of thermal injuries. The cellular changes associated with burn healing process mediated by the plant were investigated. Methods and Results: Treated rabbits with dried hexane extract exhibited increase in percentage of burn contraction as compared to control. The data showed that the expression of HSP70 was higher in treated groups with the plant extract than control groups. On other hand the expression of iNOS was higher in control groups than treated ones. It was also found that the plant extract possesses antimicrobial effect. It produced wider zones of inhibition for S. aureus and B. substilis when compared to the zones of inhibition of gram-negative isolates. And also MIC and MBC for the gram-positive bacteria were significantly lower (p < 0.05) than those of gram-negative bacteria. Conclusion: It was concluded that the positive outcomes for healing from burns is due to the over expression of HSP70, low production of iNOS and also to the antimicrobial effect of the extract.